Dampak Pelatihan Dosen terhadap Proses Belajar Mengajar Mahasiswa Jurusan Administrasi Bisnis Politeknik Negeri Pontianak - Abdullah; Herdiansyah, Dedi (Universitas Brawijaya, Indonesia, 2009)
The objective of this research is to measure the changing in respondents' work behavior after having participated in work training; to find out whether the work behavior changes as expected and how big the changing. The analysis method of this finding is descriptive and verificative toward collected data, then manipulated based on the questionnaire result. This research has one variable-training-consists of three indicator; upgrading skills and knowledge, working ability, behavior and attitude changing. The dependent variable of this research is teaching and learning process in Pontianak State Polytechnic. The findings show that (a) the upgrading skills and knowledge has little influence on teaching and learning process. It can be seen from regression value 0.0471 and its correlation value 0.051, (b) working ability has significant impact toward teaching and learning process in business administration department. It can be seen from regression value 0.511 and correlation value 0.455. The achievement indicator is due to teaching experience and education background of most lecturers (master degree) (c) behavior and attitude changing has insignificant toward teaching and learning process. It can be seen from regression value 0.266 and correlation value 0.277. therefore, conductive teaching and learning process between the students and the lecturers including transparent atmosphere, objectivity, and discipline.